A Group of Metalwork of the Artukid Period at Hasankeyf Museum - Demir, Hazal Ceylan Öztürker (Fırat University, 2022)
Metal art, which represents an important branch in handicrafts and develops with an uninterrupted production line, is important in that it contains many dynamics regarding the artistic perspective of the period and geography in which it was produced. Metal artifacts, which are portable cultural assets, represent a special group in which interaction with geographically contacted different cultures and exchange border of art are revealed. It is known that the most magnificent works in the name of metal art in medieval Anatolia were given in the mining workshops that developed on the Konya and Artukid dominance site. The Artuqids Period, which constitutes the period limit of our study, points to a special period in which numerous metal works related to artistic principles are given with the rich metal deposits in the geography where it spreads and the mining workshops established in parallel with this. Artukid Period metal contributed to the emergence of a some regional stylistic features in Anatolian metal art with differences in construction and decoration techniques. Six artifacts belonging to the Artuqid Period, which are the subject of our study, were selected from among the metal artifacts in the Hasankeyf Museum, which was established in 2019, and included in the study. The works were evaluated in terms of the materials, techniques, forms, decorations and writing elements used and tried to be introduced in all aspects within the discipline of art history.

El sanatları içerisinde önemli bir kolu temsil eden ve kesintisiz bir üretim çizgisiyle gelişen maden sanatı, üretildiği dönem ve coğrafyanın sanatsal bakış açısına dair pek çok dinamiği içerisinde bulundurması açısından önem teşkil etmektedir. Taşınabilir kültür varlıkları niteliğindeki madeni eserler, coğrafi olarak temasta olunan farklı kültürlerle etkileşimin ve sanatın sınır alışverişinin gözler önüne serildiği özel bir grubu temsil etmektedir. Orta Çağ Anadolu’sunda maden sanatı adına en görkemli eserlerin, Konya ve Artuklu hâkimiyet sahasında gelişen maden atölyelerinde verildiği bilinmektedir. Çalışma konumuzun dönem sınırını oluşturan Artuklular Dönemi, yayılım gösterdiği coğrafya içerisinde yer alan zengin maden yatakları ve buna paralel olarak kurulan maden atölyeleri ile sanatsal ilkelere bağlı sayısız madeni eser örneklerinin verildiği özel bir periyodu işaret etmektedir. Artuklu Dönemi maden sanatı, yapım ve süsleme tekniklerindeki farklılıklar ile Anadolu maden sanatı içerisinde bölgesel birtakım üslup özelliklerinin doğuşuna katkıda bulunmuştur. Çalışmamıza konu olan altı eser, 2019 yılında kurulan Hasankeyf Müzesinde yer alan madeni eserler arasında Artuklu Dönemine ait eserlerin tespiti ile çalışmaya dâhil edilmiştir. Eserler, kullanılan malzeme, teknik, form, süsleme ve yazı unsurları açısından değerlendirmeye alınarak, sanat tarihi disiplini içerisinde bütün yönleriyle tanıtılmaya çalışılmıştır.
HASANKEYF MÜZESİNDE BULUNAN ARTUKLU DEVRİNE AİT BİR GRUP MADENİ ESER